Respuestas
Respuesta dada por:
2
Saludos,
Estos son los pasos a seguir
1-2 ( 4 - 3( x - 1 ))=4 ( x - 5 ) - 1
1-2( 4 -3x+3) = 4x-20-1
1-2( 7-3x) = 4x-21
1-14+6x = 4x-21
-13+6x= 4x-21
6x-4x=-21+13
2x=-8
x=-4
De nada.
Respuesta dada por:
2
☘ TAREA :
* 1-2 ( 4 - 3( x - 1 ))=4 ( x - 5 ) - 1 ??
☘ RESPUESTA: X=-4
☘ Explicación Paso a Paso:
1-2(4-3(X-1))=4(X-5)-1
1-2(4-3X+3)=4X-20-1
1-2(7-3X)=4X-21
1-14+6X=4X-21
-13+6X=4X-21
6X-4X=-21+13
2X=-8
X=-4
Amigo espero haberte ayudado saludos!!
oscar10243
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años